Tatuagens literárias: o corpo como suporte para o texto poético - Carneiro, Jessica Torquato (2018)
Literary works are absorbed by the public and are often transformed into various types of artistic expression, such as cinema, theater, painting, sculpture, among others. As it is discussed in this paper, tattoos are also influenced by literature. This research aims to explore how literature marks human bodies by accessing what people who have these types of tattoos say about the decision to bear a specific text on their skin, verbal or non-verbal. The theoretical basis that permeates this research is the historical record of conceptions about the body, mainly based on Corbin, Courtine and Vigarello (2005[2008]). The practice of corporal modifications and tattoo history are present themes, focusing especially on Pires (2005), Marques (1997) and Gilbert (2000). Psychoanalysis also offers important contributions to the discussion, especially in subjects such as the unconscious, language, self-image and body marks. The subjectivity that exists in the definition of literature is another relevant point, because understanding what is considered as ―literature‖ contributes to the definition of what is considered a ―literary tattoo‖. This theme is mostly based on Eagleton (1985[2006]). Five tattoos are analyzed, inspired by three poems and a novel: ―A Virgem Maria‖ (1930) by Manuel Bandeira, ―Poeminho do contra‖ (1973) by Mário Quintana, ―Amor sem saída‖ (2013) by Pedro Gabriel, and Frankenstein (1831[s/d]) by Mary Shelley. The participants’ speeches are analyzed in order to observe how the literary text is blended with their lives and how they have found, on the skin, a space to express their relationship with the poetic text, which means a link between body, psyche and literature. Due to the fact that it is a type of artistic expression that occurs (almost) indelibly on the skin, a literary tattoo stimulates rich discussions about how literature leaves marks in people’s minds and bodies.